Analysis Of The Application Of Zakat Nabath (Agricultural Zakat) In Gondang Lumayang Village, Lembah Lubuk Manik Subdistrict - Siregar, Winda Sari; Sarmiana Batubara (Prodi Manajemen Zakat dan Wakaf Fakultas Ekonomi dan Bisnis Islam, 2025)
The wealth paid for zakat will not simply disappear, but instead will increase, grow, and develop. The wealth paid for zakat can also make the wealth pure and blessed. The implementation of zakat is one of the worship that is related to individuals so that its distribution is truly guided by the principles of humanity. This research is a descriptive qualitative approach, to obtain the understanding of the Gondang Lumayang Community regarding agricultural zakat through interviews. The Gondang Lumayang Community consists of 150 heads of households, most of whom make a living as farmers. There are some who have their own rice fields, but there are also rice fields that are rented. This study aims to determine how the concept is applied by the community in paying agricultural zakat, what are the obstacles in paying agricultural zakat, and what solutions to overcome these obstacles. The results of this study are that farmers in Gondang Lumayang village have paid zakat, but not in accordance with the provisions of zakat. Some of them give alms to the mosque after the harvest due to the lack of understanding in paying agricultural zakat.